Significance of Rat Mammary Tumors for Human Risk Assessment. (February 2015) - Russo, Jose
We have previously indicated that the ideal animal tumor model should mimic the human disease. This means that the investigator should be able to ascertain the influence of host factors on the initiation of tumorigenesis, mimic the susceptibility of tumor response based on age and reproductive history, and determine the response of the tumors induced to chemotherapy. The utilization of experimental models of mammary carcinogenesis in risk assessment requires that the influence of ovarian, pituitary, and placental hormones, among others, as well as overall reproductive events are taken into consideration, since they are important modifiers of the susceptibility of the organ to neoplastic development. Several species, such as rodents, dogs, cats, and monkeys, have been evaluated for these purposes; however, none of them fulfills all the criteria specified previously. Rodents, however, are the most widely used models; therefore, this work will concentrate on discussing the rat rodent model of mammary carcinogenesis.